Sumber Daya Manusia dalam Lingkungan Bisnis Global Kompetitif - Antonius Atosökhi Gea (Bina Nusantara University, 2014)
Global competition in the world of business today and in the future is inevitable. Whether it is liked or not, ready or not, the competition must be faced. There are diference attitudes in facing this situation. Countries which are ready will see it as an opportunity, but it is not always be the same for the developing or poor countries. The increasing of global competition is very widely supported by the development of technology, especially information technology. In this case the Internet occupies the most important part that relies on speed. Although there are many important things in the course of the competition, including the technology, human resources are something very decisive, the determinant key to be actively involved and to win the competition. Therefore, the model of human resource development should be more advanced than before. In this case, the role of Human Resources Management (HRM) is crucial. This section (HRM) should be able to play role to maximize productivity, ensure the quality of employment, and ultimately generates profits through proper management of human resources within the company.